2013
DOI: 10.1093/rheumatology/kes390
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of coeliac disease in patients with systemic sclerosis: a cross-sectional study of a registry cohort

Abstract: Contrary to the only two previously published studies, the low prevalence of CD that we found does not suggest that concurrent CD is a common cause of gastrointestinal complaints in SSc patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Autoantibody screening revealed anti‐tissue transglutaminase antibody. Three prior studies also revealed that coeliac disease is more frequent in SSc patients than in the general population (4–8% vs. 1%); most of their SSc patients had asymptomatic coeliac disease . Altogether, because coeliac disease is associated with increased risk of lymphoma, our findings suggest that coeliac antibody screening tests (anti‐tissue transglutaminase antibody) may be useful for disclosing coeliac disease at early stage in patients with SSc.…”
Section: Discussionsupporting
confidence: 62%
“…Autoantibody screening revealed anti‐tissue transglutaminase antibody. Three prior studies also revealed that coeliac disease is more frequent in SSc patients than in the general population (4–8% vs. 1%); most of their SSc patients had asymptomatic coeliac disease . Altogether, because coeliac disease is associated with increased risk of lymphoma, our findings suggest that coeliac antibody screening tests (anti‐tissue transglutaminase antibody) may be useful for disclosing coeliac disease at early stage in patients with SSc.…”
Section: Discussionsupporting
confidence: 62%
“…These two studies were limited by small sample sizes (n=30 and n=50) [ 15 , 16 ]. The third study, conducted by Forbess et al , tested 72 SSc patients for celiac disease serology then biopsy [ 17 ]. They reported the prevalence of celiac antibodies in SSc population as 3/72 (4%), but no cases of celiac disease confirmed by biopsy were seen in their SSc cohort [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third study, conducted by Forbess et al , tested 72 SSc patients for celiac disease serology then biopsy [ 17 ]. They reported the prevalence of celiac antibodies in SSc population as 3/72 (4%), but no cases of celiac disease confirmed by biopsy were seen in their SSc cohort [ 17 ]. They also found no important differences with respect to GI symptoms in the celiac antibody-positive compared with antibody-negative SSc patients.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados da literatura quanto à prevalência da doença celíaca (DC) na ES têmse mostrado algo controversos. Dois estudos diferentes acharam uma prevalência de aproximadamente 8% de DC na ES, enquanto que num estudo retrospectivo, Forbess et al 17 estudou a prevalência da doença celíaca em doentes com ES, associando sintomatologia gastrointestinal com os autoanticorpos característicos da doença celíaca (Ac anti-transglutaminasa, anti-gliadina e anti-endomíssio), não se tendo verificado diferenças em relação ao grupo controlo, defendendo que o rastreio desta patologia não está indicado nos doentes com ES 17 .…”
Section: Estômagounclassified